Physiological and transcriptomic analyses revealed the change of main flavor substance of Zygosaccharomyces rouxii under salt treatment - Pei, Rongqiang; Lv, Gongbo; Guo, Binrong; Li, Yuan; Ai, Mingqiang; He, Bin; Wan, Runlan (Frontiers in Nutrition, 2022)
Zygosaccharomyces rouxii was a highly salt-tolerant yeast, playing an important role in soy sauce fermentation. Previous studies reported that Z. rouxii under salt treatment produces better ferment food. However, the detailed change of main flavor substance was not clear. In this study, the physiological and transcriptomic analyses of Z. rouxii under salt treatment was investigated. The results revealed the high salt tolerance of Z. rouxii. Analysis of physiological data showed that the proportion of unsaturated fatty acids was significantly increased with the increment of salt concentrations. The analysis of organic acids showed that the content of succinic acid was significant higher in the salt-treated Z. rouxii while oxalic acid was only identified at the 18% salt concentration-treated group. Results of volatile substances analysis showed that 3-Methyl-1-butanol and phenylethyl alcohol were increased with the increment of salt concentrations. A comparison of transcriptome data showed that the genes involved in the TCA cycle and the linoleic acid synthesis process exhibited different expressions, which is consistent with the results of physiological data. This study helps to understand the change of main flavor substance of Z. rouxii under salt treatment and explore the main flavor material ingredients during food fermentation.